Impact of amoxicillin therapy on resistance selection in patients with community-acquired lower respiratory tract infections: a randomized, placebo-controlled study. - Malhotra-Kumar, S; Van Heirstraeten, L; Coenen, S; Lammens, C; Adriaenssens, N; Kowalczyk, A; Godycki-Cwirko, M; Bielicka, Z; Hupkova, H; Lannering, C; Mölstad, S; Fernandez-Vandellos, P; et al. (Oxford University Press, 2016)
Objectives To determine the effect of amoxicillin treatment on resistance selection in patients with community-acquired lower respiratory tract infections in a randomized, placebo-controlled trial. Methods Patients were prescribed amoxicillin 1 g, three times daily (n=52) or placebo (n=50) for 7 days. Oropharyngeal swabs obtained before, within 48 h post-treatment and at 28–35 days were assessed for proportions of amoxicillin-resistant (ARS; amoxicillin MIC ≥2 mg/L) and -non-susceptible (ANS; MIC ≥0.5 mg/L) streptococci. Alterations in amoxicillin MICs and in penicillin-binding-proteins were also investigated. ITT and PP analyses were conducted. Results ARS and ANS proportions increased 11- and 2.5-fold, respectively, within 48 h post-amoxicillin treatment compared with placebo [ARS mean increase (MI) 9.46, 95% CI 5.57–13.35; ANS MI 39.87, 95% CI 30.96–48.78; P<0.0001 for both]. However, these differences were no longer significant at days 28–35 (ARS MI23.06, 95% CI 27.34 to 1.21; ANS MI 4.91, 95% CI24.79 to 14.62; P>0.1588). ARS/ANS were grouped by pbp mutations. Group 1 strains exhibited significantly lower amoxicillin resistance (mean MIC 2.8 mg/L, 95% CI 2.6–3.1) than group 2 (mean MIC 9.3 mg/L, 95% CI 8.1–10.5; P<0.0001). Group 2 strains predominated immediately post-treatment (61.07%) and although decreased by days 28–35 (30.71%), proportions remained higher than baseline (18.70%; P=0.0004). Conclusions By utilizing oropharyngeal streptococci as model organisms this study provides the first prospective, experimental evidence that resistance selection in patients receiving amoxicillin is modest and short-lived, probably due to ‘fitness costs’ engendered by high-level resistance-conferring mutations. This evidence further supports European guidelines that recommend amoxicillin when an antibiotic is indicated for community-acquired lower respiratory tract infections.